FEATURES AND ORGANIZATION OF PROJECT FINANCING - Iryna Yasinovska (Фінансовий простір, 2023)
The article substantiates the importance of project financing for the national economy in the difficult conditions of Ukrainian realities. Advantages, stages of organization of project financing, peculiarities of assessment of the feasibility of project implementation, and its expertise have been studied. Considered the importance of project monitoring, and risk assessment. Directions for the activation of certain types of project financing in Ukraine are proposed.